2017
DOI: 10.3390/rs9060604
|View full text |Cite
|
Sign up to set email alerts
|

Do Daily and Seasonal Trends in Leaf Solar Induced Fluorescence Reflect Changes in Photosynthesis, Growth or Light Exposure?

Abstract: Solar induced chlorophyll fluorescence (SIF) emissions of photosynthetically active plants retrieved from space-borne observations have been used to improve models of global primary productivity. However, the relationship between SIF and photosynthesis in diurnal and seasonal cycles is still not fully understood, especially at large spatial scales, where direct measurements of photosynthesis are unfeasible. Motivated by up-scaling potential, this study examined the diurnal and seasonal relationship between SIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 49 publications
2
21
1
1
Order By: Relevance
“…Our results report linear relationships between the SIF metrics (i.e., SIF A , SIF B , and SIF A+B ) and YII, and between SIF and ETR, primarily during the mature stage ( Figure 6), when canopy chlorophyll levels and Cl red were highest. Prior investigations [42,44] have reported that YII correlates well with SIF Ay for C3 canopies, which our findings did not support for corn, a C4 crop.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our results report linear relationships between the SIF metrics (i.e., SIF A , SIF B , and SIF A+B ) and YII, and between SIF and ETR, primarily during the mature stage ( Figure 6), when canopy chlorophyll levels and Cl red were highest. Prior investigations [42,44] have reported that YII correlates well with SIF Ay for C3 canopies, which our findings did not support for corn, a C4 crop.…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, similar diurnal patterns and positive linear relationships between GPP and SIF A were reported using field and satellite observations for C3 and C4 canopies [36,37,[42][43][44][45]50]. Based on the established correlations between diurnal observations (i.e., 8:45-16:45), we also report strong positive correlations to GPP for SIF A and SIF B .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations